1980
DOI: 10.1172/jci109770
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Purification, and Partial Characterization of an Organic Anion Binding Protein from Rat Liver Cell Plasma Membrane

Abstract: A B S T R A C T Uptake of bilirubin, sulfobromophthalein (BSP), and other organic anions by the liver is a process with kinetics consistent with carrier mediation. The molecular basis ofthis transport mechanism is unknown. In the search for the putative organic anion carrier or receptor, the interaction of BSP with rat liver cell plasma membrane (LPM) has been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
4

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 39 publications
0
56
4
Order By: Relevance
“…Further evidence for similarity derives from their identical sialic acid content, the 4 mol/mol of protein dimer reported above corresponding to the 2 mol/mol of 55,000-D subunit reported for OABP (14). Finally, in preliminary experiments, an antibody to OABP cross-reacted with a sample of the intact, 105,000-D BSP/bilirubin-binding protein.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Further evidence for similarity derives from their identical sialic acid content, the 4 mol/mol of protein dimer reported above corresponding to the 2 mol/mol of 55,000-D subunit reported for OABP (14). Finally, in preliminary experiments, an antibody to OABP cross-reacted with a sample of the intact, 105,000-D BSP/bilirubin-binding protein.…”
Section: Resultsmentioning
confidence: 61%
“…Despite some evidence of overlapping specificities (5-7), this system is distinct from the principal bile acid transport mechanism (1,8,9). Studies of rat liver plasma membranes (LPM) have demonstrated the specific binding of BSP to a high-affinity binding site (10), and isolation of liver cell membrane proteins with high affinities for BSP and bilirubin has been reported by several groups (11)(12)(13)(14). The present report describes further studies of a BSP-binding membrane protein from rat liver, and the use of a rabbit antibody to this protein to demonstrate both its identity to the bilirubin-binding protein described earlier (13) and its role in the specific binding of BSP and bilirubin to rat LPM.…”
mentioning
confidence: 99%
“…Unidirectional pH gradients were formed to determine the effect of cellular pH on initial uptake of 36C1. There was no effect of inwardly or outwardly directed gradients of pH (6)(7)(8) tein; n = 3, P > 0.05). However, initial uptake of "S-BSP with an inwardly directed H' gradient (n = 4) (outwardly directed OH-gradient) was approximately twice that with an outwardly directed H' gradient (n = 4) (inwardly directed OH-gradient) (P < 0.02) (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…DISCUSSION Bilirubin uptake by the liver is a rapid process of high specificity that has kinetic characteristics which suggest carrier-mediation (3,5). The nature of the carrier is unknown, although several candidates have been identified and purified from rat liver cell plasma membrane preparations (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%